2022
DOI: 10.3390/nu14193979
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Turmeric Extract on Muscle Atrophy in Dexamethasone-Treated Mice and Myotubes

Abstract: Sarcopenia is the decline in skeletal muscle mass, strength, and functions, which decreases the quality of life in elderly people. This study investigated the suppressive effect of turmeric (Curcuma longa) extract (TE) on muscle atrophy in dexamethasone (DEX)-treated mice and C2C12 myotubes. DEX treatment significantly decreased the muscle weight and significantly increased Fbxo32 and Murf1 expression in mice, and these changes were suppressed by the supplementation of an AIN-93 based diet with 2% TE. A simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Conversely, supplementation with Cur significantly attenuated muscle protein degradation [ 82 ]. Dietary supplementation of Cur inhibited the expression of MAFBX and MURF1 when dexamethasone induced muscle atrophy in mice [ 83 ]. However, study in neuroblastoma (NB) demonstrated that Cur supplementation can inhibit cell proliferation by promoting the expression of Foxo3a and leading to cell apoptosis This may be related to the difference between tumor cells and normal cells [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, supplementation with Cur significantly attenuated muscle protein degradation [ 82 ]. Dietary supplementation of Cur inhibited the expression of MAFBX and MURF1 when dexamethasone induced muscle atrophy in mice [ 83 ]. However, study in neuroblastoma (NB) demonstrated that Cur supplementation can inhibit cell proliferation by promoting the expression of Foxo3a and leading to cell apoptosis This may be related to the difference between tumor cells and normal cells [ 84 ].…”
Section: Discussionmentioning
confidence: 99%